Evaluating the Impact of Managerial Decisions on Production Costs Using the Leveling of Effective Factors - Ghashghaei, Mohammad Taghi; Ahmadimousaabad, Aiyob; Taleghani, Mohammad (Management Strategies and Engineering Sciences, 2024)
the aim of this study was to assess the impact of internal and external decisions on the cost of industrial products. the research method is applied and quantitative. the statistical population of the study is experts and experts in academia and industry that 25 people were selected as the sample size by theoretical saturation method. a researcher - made questionnaire was used to collect data. validity was confirmed by experts and reliability was confirmed by cronbach 's alpha. the results of quantitative data were analyzed by interpretive approach. the results showed that a total of 31 factors in the five categories of sales and marketing factors, investment factors, production factors, legal factors and price elasticity factors have an important role in the cost of industrial products that were placed in levels 2, 1, 4, 4 and 3, respectively. therefore, when making decisions about determining the cost of the products in question, continuous attention should be paid to these internal and external factors.